2021
DOI: 10.1101/2021.08.31.21262917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological antecedents towards COVID-19 vaccination using the Arabic 5C validated tool: An online study in 13 Arab countries

Abstract: Background and aim: Following emergency approval of vaccines, the amount of scientific literature investigating population hesitancy towards vaccination against the novel coronavirus disease (COVID-19) has increased exponentially. Nevertheless, the associated psychological behaviors with this phenomenon are still not clearly understood. This study aims to assess the psychological antecedents of the Arab population toward COVID-19 vaccines. Methods: A cross-sectional, online study using a validated Arabic versi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…The 5C Scale was previously used in the Arab population including KSA to explore vaccine acceptance and intentions during the COVID-19 pandemic (56). Results in the present study revealed that the highest mean score for any of the antecedents of vaccination was for collective responsibility.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The 5C Scale was previously used in the Arab population including KSA to explore vaccine acceptance and intentions during the COVID-19 pandemic (56). Results in the present study revealed that the highest mean score for any of the antecedents of vaccination was for collective responsibility.…”
Section: Discussionmentioning
confidence: 54%
“…In their analysis, the highest reported antecedent by category in KSA was confidence, followed by collective responsibility, calculation, complacency, and finally constraints. Their results suggested that respondents in KSA showed high confidence in COVID-19 vaccines, when compared to other countries, as was found in UAE and Kuwait (56). That pattern likely represented the active vaccination programs in these countries.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations